The SR splicing factors ASF/SF2 and SC35 have antagonistic effects on intronic enhancer-dependent splicing of the beta-tropomyosin alternative exon 6A. - Gallego, M E (1997)
Exons 6A and 6B of the chicken beta-tropomyosin gene are mutually exclusive and selected in a tissue-specific manner. Exon 6A is present in non-muscle and smooth muscle cells, while exon 6B is present in skeletal muscle cells. In this study we have investigated the mechanism underlying exon 6A recognition in non-muscle cells. Previous reports have identified a pyrimidine-rich intronic enhancer sequence (S4) downstream of exon 6A as essential for exon 6A 5'-splice site recognition. We show here that preincubation of HeLa cell extracts with an excess of RNA containing this sequence specifically inhibits exon 6A recognition by the splicing machinery. Splicing inhibition by an excess of this RNA can be rescued by addition of the SR protein ASF/SF2, but not by the SR proteins SC35 or 9G8. ASF/SF2 stimulates exon 6A splicing through specific interaction with the enhancer sequence. Surprisingly, SC35 behaves as an inhibitor of exon 6A splicing, since addition to HeLa nuclear extracts of increasing amounts of the SC35 protein completely abolish the stimulatory effect of ASF/SF2 on exon 6A splicing. We conclude that exon 6A recognition in vitro depends on the ratio of the ASF/SF2 to SC35 SR proteins. Taken together our results suggest that variations in the level or activity of these proteins could contribute to the tissue-specific choice of beta-tropomyosin exon 6A. In support of this we show that SR proteins isolated from skeletal muscle tissues are less efficient for exon 6A stimulation than SR proteins isolated from HeLa cells.